Transformational Leadership, Digital Literacy, Propensity to Trust, and Creativity of MSMEs: Mediating Effects of Knowledge Sharing - Pertiwi, Wike; Setyawati, Sri Murni; Anggraeni, Ade Irma (The Journal of Behavioral Science, 2023)
Amid the burgeoning creative industries in Indonesia, a gap exists in comprehending the intricate connections between transformational leadership, digital literacy, trust, knowledge sharing, and employee creativity, underscoring the need for research to navigate these uncharted dimensions of fostering innovation. Data were collected from 235 women-led micro, small, and medium enterprises (MSMEs) in the creative sector in West Java, Indonesia. The researchers utilized the structural equation modeling (SEM) technique to analyze the data. The results indicated that transformational leadership positively effect to employee creativity (β= 0.25, p= 0.00). Additionally, knowledge sharing acted as a mediator between transformational leadership and employee creativity (β= 0.17, p= 0.00). Similarly, knowledge sharing mediated the relationship between digital literacy and employee creativity (β = 0.21, p = 0.02). The study also found a positive association between propensity to trust and employee creativity (β = 0.12, p = 0.03), with knowledge sharing playing a mediating role (β = 0.14, p = 0.01). These insights hold significant implications for behavioral science. They underscore the pivotal roles played by transformational leadership, digital literacy, trust-building, and knowledge sharing in stimulating and nurturing employee creativity within the dynamic context of creative industries. Business leaders and managers can utilize these insights to guide the development of strategies that foster creativity and innovation within organizations.